Sorjan method for producing vegetables, fruits, and fish together with the changing climate in coastal Bangladesh - Ahmed, Sharif; Devnath, Manik; Islam, Md. Moinul (International Rice Research Institute, 2025)
The Sorjan method is an integrated sustainable farming system that harmoniously combines the cultivation of vegetables, fruits, and fish in the challenging coastal environments of Bangladesh. This approach highlights the importance of adopting Sorjan systems to enhance resilience against changing climate patterns, such as increased salinity, erratic rainfall, and rising sea levels. By integrating aquaculture with horticulture, the Sorjan method promotes diversified production, improves nutrient cycling, and optimizes the use of land and water resources. This system offers multiple benefits, including increased income, better nutrition, and improved adaptation to climate change. Additionally, it helps mitigate environmental degradation by reducing dependence on chemical inputs and harnessing natural ecological processes. We emphasize cost-effective production systems. Promoting awareness and knowledge sharing about Sorjan methodologies can empower local communities to adopt sustainable practices, ensuring food security and climate resilience. Ultimately, this approach supports the sustainable development goals of increased productivity, environmental sustainability, and community well-being in the vulnerable coastal regions of Bangladesh.